Evaluation of the lithospheric magnetic field mapped by the first year of MSS-1 data - S. Williams; D. Gubbins; P. W. Livermore; Y. Jiang (Earth and Planetary Physics)
The MSS-1 satellite began mapping Earth’s magnetic field in November 2023. Here, we perform a preliminary assessment of the new information provided on Earth’s lithospheric magnetic field from the first 12 months of data from MSS-1. We analyze data from the low-inclination orbital tracks of MSS-1 alongside data collected contemporaneously by the Swarm mission, and compare these to models for the lithospheric field from older satellite data and to predictions from models of lithospheric magnetization from tectonic constraints. We find that 1 year of data grouped into geographical bins is sufficient to produce a robust map of lithospheric anomalies. Time series analysis reveals that bins further from the equator arrive at stable values more rapidly, while equatorial regions require 9−10 months of data accumulation for stable signal recovery. The mapped data agree well with older satellite models and with predictions from a lithospheric magnetization model, with the largest mismatches suggesting that models of continental magnetization in particular require further revision. These results demonstrate the value of MSS-1’s unique orbital configuration in complementing existing satellite magnetic field measurements.